The Regulation on Matrimonial Property and Its Operation in Succession Cases — Its Interaction with the Succession Regulation and Its Impact on Non-participating Member States - Bonomi, Andrea (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The Regulations on Matrimonial Property (No 2016/1103) and on the Property Consequences of Registered Partnerships (No 2016/1104) are new important pieces in the “puzzle” of European private international law. This article particularly focuses on the relationship between the Matrimonial Property Regulations and the Succession Regulation, two instruments which will often be applied in parallel because of the close connection between the two areas they govern. The author examines in particular the scope of those instruments as well as their interaction with respect to jurisdiction and applicable law. At the same time, an attempt is also made to assess the position of Poland and of those other Member States that are bound by the Succession Regulation, but not by the Matrimonial Property Regulation.